Secreted Frizzled-Related Protein 5 Protects Against Cardiac Rupture and Improves Cardiac Function Through Inhibiting Mitochondrial Dysfunction - Huang, Xin; Yan, Yan; Zheng, Wen; Ma, Youcai; Wang, Xiao; Gong, Wei; Nie, Shaoping (Frontiers in Cardiovascular Medicine, 2021)
Background: Secreted frizzled-related protein 5 (Sfrp5) has been suggested to be a protective regulatory protein in coronary heart disease. However, the role of Sfrp5 in regulating ischemic injury and its consequences is not known. The aim of our study was to explore the effects of Sfrp5 on hearts after myocardial infarction (MI) and to investigate the underlying mechanisms. Methods and Results: We found Sfrp5 was down-regulated over time in the heart tissue of MI mice. To further elucidate the role of Sfrp5 during MI, we established a cardiac overexpression of Sfrp5 mice model via using the cardiotropic adeno-associated virus serotype 9 (AAV9). Overexpression of Sfrp5 significantly reduced infarct size as demonstrated by a decrease in mortality owing to cardiac rupture. Moreover, cardiac overexpression of Sfrp5 increased left ventricular function and mitochondrial biogenesis, decreased cardiomyocyte apoptosis, suppresses inflammation reaction, inhibition of oxidative stress, and ameliorated cardiac remodeling as demonstrated by left ventricular ejection fraction, mitochondrial morphology, heart weight, NADH oxidase activity levels, and myocardial fibrosis at 2 weeks post-MI. At the molecular level, overexpression of Sfrp5 significantly increased the expression of p-AMPKThr172 protein with higher expression of mitochondrial fusion protein (Mfn1 and Mfn2) and lower expression of mitochondrial fission protein (p-Drp1Ser616/Mid49/MFF/Fis-1). In isolated neonatal rat cardiac myocytes, Sfrp5 treatment attenuated hypoxia-induced mitochondrial dysfunction. Inhibition of AMPK activity with compound C abrogated this benefit. Conclusions: Sfrp5 overexpression inhibits ischemic injury, reduced risk of cardiac rupture, ameliorates post-MI remodeling and decreases the progression to heart failure via disrupting mitochondrial dysfunction and partly through normalizing the AMPK activity.